Surgical management of oral submucous fibrosis in an edentulous patient: A procedural challenge - Mahajan, Amit D. (Medknow Publications, 2010)
Prosthetic rehabilitation of patients with oral submucous fibrosis (OSMF) offers a formidable challenge due to restricted mouth opening. Physiotherapy via interocclusal force application is the mainstay for surgical treatment. Herein, we report a case of a man with OSMF requiring construction of dentures. The main objective was to deliver intra-operative and post operative inter occlusal forces without fracturing the mandible and thus providing rehabilitation to the patient prosthetically. An edentulous male patient reported with grade IVA OSMF to our department to improve his mouth opening for denture construction. The patient was managed successfully using surgical sectioning of the fibrous bands. Inter occlusal force application for mouth opening during the operation and post operative physiotherapy were facilitated using custom-made occlusal splints. Satisfactory mouth opening was achieved, with good healing and no event of infection or fracture. Here, we propose an easy method to achieve adequate mouth opening in an edentulous patient of OSMF, with atrophic ridges; without the chances of fracture of either jaw.